Sustainable spill cleanup - Gimpelson, Laura (Knovel, 2011)
Sustainable remediation practices can be used to reduce the adverse impact caused by spills of any size in any locale, even in middle of the ocean. The goal of every spill cleanup is to contain and control the spill, limit immediate impacts and minimize long-term cleanup efforts. Selecting the sustainable response and short-term remediation options are only part of developing a sustainable spill response plan. Sustainability must be part of the planning and prevention process as well.